Knowledge, Attitude and Practices Slaughterhouse Management in Special Capital Region of Jakarta - Sidablok, Hasudungan Agustinus; -, Macfud; -, Nahrowi; Pandjaitan, Nurmala K (Sodality: Jurnal Sosiologi Pedesaan, 2018)
The objective of this research is understanding the correlation of characteristics with level of knowledge, attitude, and practice of slaughterhouse management concerning hygiene, sanitation, and waste management.  Research objects in this study are 3 types of slaughterhouse in Jakarta; pig, poultry, and ruminant slaughterhouse.  The aim of this study is determine the correlation of knowledge, attitude, and practice characteristics of slaughterhouse management related to hygiene, sanitation, and waste management. Tools used are questionnaire to assess knowledge, attitude, and practices of slaughterhouse management. Data collected consist by questionnaire filled by slaughterhouse agency. Data were analysed with SPSS® to calculate characteristic and variables correlation. On pig slaughterhouse management, there is correlation between educational background with knowledge (P<0.05; r=-0.804). On ruminant slaughterhouse, there is a correlation between income level with practice (P<0.05; r=-0.804) and knowledge level with attitude (P<0.05; r=0.641). On poultry slaughterhouse, there is a clear correlation between educational level with knowledge (P<0.05; r=0.686), income level with knowledge (P<0.06; r=-0.802), educational level with attitude (P<0.05; r=0.716), frequency of training with attitude (P<0.05; r=-0.741), frequency of training with practice (P<0.05; r=0.758), and employment status with practice (P<0.05; r=0.127). Training and socialization frequency must be improved especially for ruminant slaughterhouse for it is the location with the least number of training and socialization. Education level requirement for employment must also be increased since education level has a clear correlation with knowledge.